Introducing world Christianity - Farhadian, Charles E. 1964- (Chichester, West Sussex Wiley-Blackwell, 2012)
"This is an engaging multidisciplinary introduction to the worldwide spread and impact of Christianity. Bringing together chapters from leading scholars in history, sociology, anthropology, and religious studies, this book examines the major transformations in contemporary societies brought about through the influence of Christianity. Each chapter shows how the broad themes within Christianity have been adopted and adapted by Christian denominations within each major region of the world. So, the book paints a global picture of the impact of Christianity, enriched by detailed historic and ethnographic material for each particular region. Throughout, the chapters examine Protestant, Evangelical, Catholic and Orthodox forms of Christianity. However, the approach is non-theological, focusing on the impact of and response to Christianity, rather than questions of faith. The combination of broader perspectives and deep analysis of particular regions, illuminating the social, cultural, political, and religious features of changes brought about by Christianity, makes this book essential reading for students of world Christianity"-- Provided by publisher
Christianity in South Asia : negotiating religious pluralism Christianity in Latin America : changing churches in a changing continent Brazilian charisma : pentecostalized Christianity in Latin America's largest nation Central America and the Caribbean : Christianity on the periphery Christianity in North America : changes and challenges in a land of promise Christianity in Australia and New Zealand : faith and politics in secular soil Christianity in East Asia : evangelicalism and the March first independence movement in Korea Christianity in Southeast Asia : similarity and difference in a culturally diverse region Christianity in Polynesia : transforming the islands Christianity in Eastern Europe : a story of pain, glory, persecution, and freedom Christianity in Micronesia : the interplay between church and culture Christianity in Western Europe : mission fields, old and new? West African Christianity : padres, pastors, prophets, and Pentecostals / Ogbu Kalu -- Christianity in Southern Africa : the aesthetics of well-being Christianity in Melanesia : transforming the warrior spirit Christian belongings in East Africa : flocking to the churches Middle Eastern and North African Christianity : persisting in the lands of Islam Ian Breward -- Garry W. Trompf Marion Maddox -- Francis X. Hezel -- R. Andrew Chesnut -- Samuel Escobar -- Virginia Garrard-Burnett -- Kevin J. Christiano -- Timothy S. Lee -- Barbara Watson Andaya -- Arun Jones -- Peter Kuzmic -- Simon Coleman -- Frederick Klaits -- Ben Knighton -- Heather J. Sharkey --
Includes bibliographical references and index.
Keywords: Christianity